2019
DOI: 10.1080/19396368.2019.1645236
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of DNA cleavage produced by seminal plasma using leukocytes as a cell target

Abstract: Numerous studies have shown the presence of DNA lesions in human spermatozoa affecting sperm quality. However, the nature of this anomaly and its relationship with patient etiology are poorly understood since different mechanisms can be involved in the formation of these novel DNA configurations including the action of a seminal plasma nuclease activity. The objective of this study was to assess the capacity of seminal plasma for producing endogenous DNA cleavage using nuclei of peripheral blood leukocytes as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 63 publications
(58 reference statements)
2
8
0
Order By: Relevance
“…We do not yet have enough scientific evidence to understand the role that the DNase activity is playing in DNA degradation observed in men with SCI, but this activity cannot be discarded as a main actor in this process. In fact, in a previous investigation, our group demonstrated the capacity of seminal plasma to produce DNA degradation when leukocytes were incubated with seminal plasma of normal individuals 25 . The known capacity of DNases present in the seminal plasma to transverse the plasma membrane of leukocytes, is consistent with a putative ability of the DNases present in the seminal plasma to affect sperm DNA.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We do not yet have enough scientific evidence to understand the role that the DNase activity is playing in DNA degradation observed in men with SCI, but this activity cannot be discarded as a main actor in this process. In fact, in a previous investigation, our group demonstrated the capacity of seminal plasma to produce DNA degradation when leukocytes were incubated with seminal plasma of normal individuals 25 . The known capacity of DNases present in the seminal plasma to transverse the plasma membrane of leukocytes, is consistent with a putative ability of the DNases present in the seminal plasma to affect sperm DNA.…”
Section: Discussionsupporting
confidence: 67%
“…In fact, in a previous investigation, our group demonstrated the capacity of seminal plasma to produce DNA degradation when leukocytes were incubated with seminal plasma of normal individuals. 25 The known capacity of DNases present in the seminal plasma to transverse the plasma membrane of leukocytes, is consistent with a putative ability of the DNases present in the seminal plasma to affect sperm DNA. Oxidative stress, mainly associated with endogenous reactive oxygen species (ROS), is a common source of DNA damage.…”
Section: On the Nature Of Sperm Dna Breakssupporting
confidence: 60%
“…It has been shown that spermatozoa from several species, including humans, have an endogenous nuclease that directly participates in apoptosis (Sotolongo et al., 2005). Moreover, the presence of DNase activity at the seminal plasma can be an additional source of DNA cleavage (Cortés‐Gutiérrez et al., 2019; Sotolongo et al., 2003).…”
Section: What Are the Mechanisms Causing Sperm Dna Damage?mentioning
confidence: 99%
“…Exposure to damaging agents, including certain pesticides, chemicals, radiation, antineoplastic drugs, tobacco, or diseases such as neoplasms, infections, varicocele, and even fever episodes, may trigger SDF production, through one or several of the mechanisms previously described 12 . Furthermore, the presence of DNase has been shown to adversely affect sperm DNA 13,14 . It is also likely that some spermatozoa may be more susceptible to SDF induction, due to a failure or alteration in chromatin compaction, for example, when the protamine 1/protamine 2 ratio is altered 15 …”
Section: Introductionmentioning
confidence: 99%